Tissue-Binding Properties of the Cholera Toxin - Peterson, Johnny W. (1974)
[(125)I]choleragen was employed to study further the tissue-binding properties of highly purified choleragen. It was observed that [(125)I]choleragen was bound when combined with mucosal homogenates from all regions of the gastrointestinal tract of adult guinea pigs. Gastric, duodenal, jejunal, and ileal mucosa appeared equally effective in toxin-binding capacity. Preparations of large intestinal mucosa could bind an exceptionally larger amount of toxin. The binding property of small intestinal homogenates could not be attributed to any particular fraction after differential centrifugation; rather, the toxin receptor appeared to be associated with several sizes of particles containing cell membrane components. Although binding to mammalian cells was easily demonstrable, no binding to several types of bacterial cells was observed. The toxin receptor was found to be a “universal component” of many mammalian cell membranes, since specific binding of the toxin to a variety of guinea pig tissues was clearly demonstrated. [(125)I]choleragen binding to all tissues, with the exception of those prepared from brain and large intestinal mucosa, could be inhibited by preincubation of the tissue homogenates with unlabeled choleragen but not with comparable concentrations of normal rabbit serum proteins. The determination of the specificity of [(125)I]choleragen binding to brain and large intestinal mucosal homogenates was hampered by the continual release of soluble receptor from the homogenates, both of which contained the highest concentration of cholera toxin receptor. The data support and extend observations that cholera toxin binding to tissue receptor(s) is a very specific reaction, and further indicate that binding may occur with a variety of tissues to different degrees.